2020
DOI: 10.3390/bs10020055
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Mothers’ Postpartum Depression From Their Infants’ Cry Vocalizations

Abstract: Postpartum Depression (PPD), a condition that affects up to 15% of mothers in high-income countries, reduces attention to the needs of the child and is among the first causes of infanticide. PPD is usually identified using self-report measures and therefore it is possible that mothers are unwilling to report PPD because of a social desirability bias. Previous studies have highlighted the presence of significant differences in the acoustical properties of the vocalizations of infants of depressed and healthy mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The technique consisted of generating new synthetic samples by adding white noise to a copy of the whole or of a subset of the original sample [39,44,45]. The technique has been shown to be suitable for ML analysis and classification of different type of signals, including neurophysiological signals [27,46], and it has been successfully employed to enhance the accuracy of ML classifiers [39,47].…”
Section: Data Augmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique consisted of generating new synthetic samples by adding white noise to a copy of the whole or of a subset of the original sample [39,44,45]. The technique has been shown to be suitable for ML analysis and classification of different type of signals, including neurophysiological signals [27,46], and it has been successfully employed to enhance the accuracy of ML classifiers [39,47].…”
Section: Data Augmentationmentioning
confidence: 99%
“…Previous works have shown that Machine Learning (ML) models can be successfully employed to study neurophysiological signals. In Gabrieli et al [27], for example, different machine learning models were tested to verify the possibility of classifying infants' vocalisations while in other works the technique was shown to be suitable for the automatic identification of physiological signal quality [28,29]. Li et al [29], for example, employed Support Vector Machines (SVM) models to distinguish between clean and noisy electrocardiogram (ECG) recording.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, economic loss due to mental health disorders is an issue that requires immediate and appropriate attention [ 1 , 2 ]. In addition, early detection of depression can help to reduce the number of suicides caused by depression and prevent infanticide by mothers with postpartum depression (PPD) [ 3 ]. To address these issues, an easily accessible and low-cost mental health screening method is required.…”
Section: Introductionmentioning
confidence: 99%
“…Reporting bias refers to participants’ intentional disclosure or suppression of certain information (e.g., medical history, smoking history). PPD is usually identified using self-report measures; therefore, it is possible that mothers with PPD are unwilling to report it because of social desirability bias [ 3 ]. Further, assessment tools using biomarkers such as saliva and blood have also been studied [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation